Desain Strategi Prioritas Kebutuhan Investasi Bidang Infrastruktur di Indonesia - Rindang Matoati; Lindawati Kartika (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2017)
Based on the survey of World Economic Forum 2013-2014 lack of infrastructure improvements made Indonesia has placed ranks 82 out of 148 countries surveyed by the World Economic Forum 2013-2014. The purpose of this activity are: (a) Formulate a comprehensive and strategic analysis of investment in infrastructure, particularly in the period 2015-2019, (b) Identify and define the priority infrastructure projects that have an impact on economic growth and regional development. Data analyze using a SWOT analysis and Exponential Comparative Method (MPE) and The House Models. The study states that there are eight (8) priority sectors developed infrastructure which is divided into five (5) years from 2015 to 2019, there are three scenarios need for infrastructure investment that is optimistic, moderate and pessimistic that can be a contribution and input for the government to classify infrastructure projects that have an impact on economic growth, sector and region.